Between Psychopathology and Ideology: Challenges and Practices in Interpreting Young Extremists Experiencing Mental Illness in the Netherlands - Vermeulen, Floris; van Leyenhorst, Maarten; Roex, Ineke; Schulten, Norah; Tuzani, Najib (Frontiers in Psychiatry, 2022)
How violent extremism is interpreted among adolescents and young adults who experience a form of psychopathology can have far-reaching consequences for these youth and for society. A fundamental consideration here is the role that ideology and psychopathology play in radicalization and possibly related extremist violence. Risk management is challenged at various levels. This article seeks to contribute to academic and policy discussions on psychopathology and extremism by combining relevant insights from practices in the Netherlands. In this perspective article our aim is to stimulate awareness and research, on the basis of operational knowledge of the Dutch case, that helps professionals across the various domains of risk management with more expertise and the ability to better integrate and interact the concepts of psychopathology and ideology. We end with formulating hypotheses for further research.